Key concepts in artificial intelligence - Padallan, Jocelyn O., author (Ontario, Canada : Arcler Press, 2022)
This book explains numerous key terms that are related to Artificial Intelligence. Artificial intelligence is the simulation of human intelligence processes by machines, especially computer systems. Specific applications of AI include expert systems, natural language processing, speech recognition and machine vision.
Includes bibliographical references and index.
Keywords: Artificial intelligence